Patrimônio posto à mesa: a culinária das comunidades de Dona Francisca – RS - Reck, Daffine Natalina (2023)
The work entitled “Heritage placed on the table: the cuisine of Dona Francisca – RS communities” highlights the Gastronomy of the Municipality, having as scope the investigation of the main food productions that integrate the culinary heritage of the Franciscans, having as final product the elaboration of a notebook with the recipes chosen by the inhabitants of each community that integrates the administrative division of the Municipality. Understanding Dona Francisca's culinary practices as identifying elements of the region's cultural peculiarities, in order to interconnect food and heritage, traditions, identities and typical dishes are the objectives of this dissertation, prepared by a teacher who works in elementary education in the Municipality. The research carried out is anchored in conducting interviews with residents of the twelve Franciscan communities and their typical culinary recipes, ways of doing and how to pass on such knowledge. From this, we tried to describe the experience in Heritage Education through the insertion of aromas and flavors, transmitted through generations, in the classroom, with workshops at the Municipal School of Early Childhood Education. There was also a survey and study of community parties as elements of sociability, territorial development and dissemination of local cuisine as a form of appreciation and tourist attraction. With that, through the interviews, the typical dishes of each community were chosen, the recipes were registered and their study in relation to the local culture. The last part of the dissertation presents the description of the product, how it was built and the proposed final result, which was a book/book of recipes with the record of the history of each community and its identity dishes. With this dissertation linked to the Area of Concentration and Line of Research in History and Cultural Heritage, the aim is to perceive the cultural aspects that are present in the recipes and in their ways of making, which permeate generations, being endowed with traditions, cultures, customs and identity elements that are part of the cultural heritage of the population. With this, it is intended to insert the gastronomic knowledge of Dona Francisca as cultural heritage of the territory of Quarta Colônia as well as Unesco Geopark.